2023
DOI: 10.3390/molecules28041646
|View full text |Cite
|
Sign up to set email alerts
|

Compilation of the Antimicrobial Compounds Produced by Burkholderia Sensu Stricto

Abstract: Due to the increase in multidrug-resistant microorganisms, the investigation of novel or more efficient antimicrobial compounds is essential. The World Health Organization issued a list of priority multidrug-resistant bacteria whose eradication will require new antibiotics. Among them, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacteriaceae are in the “critical” (most urgent) category. As a result, major investigations are ongoing worldwide to discover new antimicrobial compounds. Burkholderia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 151 publications
(166 reference statements)
1
4
0
Order By: Relevance
“…We speculate that an interaction between the iodine atom and the alkyne bond present on the carbamate scaffold potentiates the activity of IPBC against S. aureus and V. parahaemolyticus. This suggestion is partially supported by the membrane disruption typical of iodine observed in this study and the reported antimicrobial effects of cepacin and caryoynecin, which both contain triple alkyne bonds, against S. aureus , E. coli, and Klebsiella pneumonia 51 .…”
Section: Discussionsupporting
confidence: 75%
“…We speculate that an interaction between the iodine atom and the alkyne bond present on the carbamate scaffold potentiates the activity of IPBC against S. aureus and V. parahaemolyticus. This suggestion is partially supported by the membrane disruption typical of iodine observed in this study and the reported antimicrobial effects of cepacin and caryoynecin, which both contain triple alkyne bonds, against S. aureus , E. coli, and Klebsiella pneumonia 51 .…”
Section: Discussionsupporting
confidence: 75%
“…In the multi-genus complex known as Burkholderia sensu lato , antimicrobial compounds have been reported ( Petrova and Mahenthiralingam, 2022 ; Rodríguez-Cisneros et al, 2023 ). This study primarily compiles the antimicrobial compounds identified in Burkholderia .…”
Section: Introductionmentioning
confidence: 99%
“…Pityriacitrin (23) is a natural marine alkaloid containing β‐carboline moiety was obtained and isolated from a Chinese Burkholderia species NBF227 serving diverse biological functions including anticancer activity (Rodríguez‐Cisneros et al., 2023). Xu et al., (2019) synthesized and designed several pityriactrin derivatives by combining β‐carboline pharmacophore with amide functional group.…”
Section: Marine Alkaloid‐oriented β‐Carboline Analoguesmentioning
confidence: 99%